Legal Consequences Of Unilateral Termination Of Distribution Contract By Principal Company Against Distributor - Wahab, Abdul (International Significance of Notary, 2024)
Abstract : A valid agreement shall apply as law to the parties. The agreement is binding on the parties and cannot be revoked or cancelled unilaterally only. If you want to withdraw or cancel it, you must obtain the consent of the other party, so it is agreed again. However, if there are sufficient reasons according to the Law, the agreement may be withdrawn or canceled unilaterally. in Article 1338 paragraph (2) of the Civil Code. states that: "such agreements shall be irrevocable other than by agreement of both parties, or for reasons which the Act declares sufficient therefor". From Article 1338 paragraph (2) of the Civil Code, it is clear that the agreement cannot be canceled unilaterally, because if the agreement is canceled unilaterally, it means that the agreement is not binding between the people who made it. Article 1266  and  article 1267 of the Civil Code which reads  "the party against whom the engagement is not fulfilled, can choose whether he, if it can still be done, will  compel the other party to fulfill the agreement, or whether he will demand the cancellation of the agreement, accompanied by reimbursement of losses and interest." So it is clearly stipulated regarding the condition of void if one of the parties does not fulfill its obligations. The cancellation must be requested to the court through a lawsuit, this is intended so that later no party can cancel the unilateral agreement on the grounds that one of the other parties does not carry out its obligations (default). One of the considerations for the cancellation of a unilateral agreement can be sued with a lawsuit against the law, because it is considered that unilateral cancellation is not based on the reasons justified according to their agreement to be canceled, and can be said to have violated their legal obligations under the law, in this case violating Article 1338 paragraph (2) of the Civil Code.Keywords : Legal Consequences, Unilateral Termination of Contract, Distributor.